Feminising Civic Engagement for Monitoring Effective Use of Public Finances in Tanzania’s Local Governments - Muya, Dominick K.; Mwakasangula , Dr Eliza (Journal of Policy and Leadership, 2018)
Despite an increased number of civic engagement that monitors effective use of public finances at the district level in Tanzania; researches show that there is a limited number of women and girls who engages in that process. This compromises the goal of ensuring women’s effective participation and equal opportunities for civic engagement. The article explored factors contributing to the persistent gender gap in access to opportunities for tracking local government use of public finances through Public Expenditure Tracking Survey (PETS). The article is a result of a study that utilized both qualitative and quantitative data from two Tanzania’s local governments in a cross-sectional dataset consisting of 232 study participants. Several contributing factors to the persistent gender gap were found. The article argues that despite Tanzania’s outstandingly successful women empowerment transition at the national level, it has never been able to translate it into the lower levels of the society such local councils where the empowerment culture is yet to be entrenched. It ends by recommending several strategies to bridge gender gap in access to opportunities for PETS through CSOs. The article also draws insights from African feminism and confronts them with empirical evidence from areas that this study was undertaken.